Design and Development of a Makeup Artist Data Management Application : Design and Development of a Makeup Artist Data Management Application - Ramadhani, Dian; Anisa, Rahmi (Institut Riset dan Publikasi Indonesia, 2025)
The growing beauty industry requires efficient management tools for Makeup Artist (MUA) teams, who often face operational challenges due to the use of manual or non-integrated digital tools. This study contributes by providing an integrated, mobile-first workflow that directly links bookings, schedules, and financial records with role-based access and automated reminders, reducing fragmentation from manual or separate tools and offering consolidated insights for MUAs’ decision-making. The application's quality was validated through Black-Box testing, achieving a 100% success rate across 35 functional test cases that covered all main features. Usability was then evaluated in a case study with a professional MUA and two team members (N=3) who used the application for one week before completing the Computer System Usability Questionnaire (CSUQ). The results yielded an overall mean score of 6.52 out of 7, indicating very high user satisfaction, with subscale scores showing that users found the system both helpful and easy to navigate. Future development may include expanding the dashboard's analytical capabilities or integrating a direct client payment gateway.